1998
DOI: 10.1046/j.1525-1497.1998.00023.x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of asymptomatic carotid bruits in the elderly

Abstract: OBJECTIVE:To determine the association between asymptomatic carotid bruits and the development of subsequent stroke in older adults with isolated systolic hypertension. DESIGN:Retrospective cohort study. SETTING:The Systolic Hypertension in the Elderly Program (SHEP), a 5-year randomized trial testing the efficacy of treating systolic hypertension in noninstitutionalized persons aged 60 years or older. From the original 4,736 SHEP participants, we identified a cohort of 4,442 persons who had no prior history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…36 Unfortunately, this protocol relies upon limited predictive power of auscultation of the cervical carotid arteries for bruits, rather than duplex ultrasound, a significantly more accurate screening method. 37,38 However, formal duplex evaluations are time consuming and expensive, and despite excellent accuracy have not been shown to be cost-effective in screening for carotid stenosis. 39 A rapid, accurate, and inexpensive 3-minute "quick scan" carotid ultrasound protocol was utilized in this study to counter this disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…36 Unfortunately, this protocol relies upon limited predictive power of auscultation of the cervical carotid arteries for bruits, rather than duplex ultrasound, a significantly more accurate screening method. 37,38 However, formal duplex evaluations are time consuming and expensive, and despite excellent accuracy have not been shown to be cost-effective in screening for carotid stenosis. 39 A rapid, accurate, and inexpensive 3-minute "quick scan" carotid ultrasound protocol was utilized in this study to counter this disadvantage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, such a modality could be used for longitudinal tracking of patient health. For all these reasons, there is a renewed impetus to transform auscultation into a quantitative and accurate method [3,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Systolic Hypertension in the Elderly study found carotid bruits to weakly predict cerebrovascular events with a relative risk of stroke of 1.3, 4 whereas the Evans County Study found a strong relationship with a relative risk of 4.1 for the combined event rate of transient ischemic attacks (TIAs) and stroke. 5 The uncertainty about the prognostic implications of a carotid bruit and the difficulty in managing asymptomatic carotid stenosis has led some organizations to recommend against routine auscultation for carotid bruits.…”
mentioning
confidence: 99%